World Bolshevism - Martov, Iulii (Athabasca University Press, 2022)
Beginning in 1903, the Russian Social Democratic Labour Party was divided into opposing sections, one led by Vladimir Lenin, the other by Iulii Martov. Until 1917, both Lenin and Martov were equally prominent figures in Russian politics. Martov, an anti-war socialist intellectual from a Jewish background, wrote prolifically for a number of important publications inside and outside Russia. Although the books, articles, and pamphlets written by Lenin during the same period remain readily available today, those by Martov are extremely hard to find in their original Russian or in translation. Following Martov's untimely death in 1923, a Russian-language edition of one of his books, World Bolshevism, was published. But it was only in 2000, after decades of extreme censorship, that parts of the book were legally published in Russia. In English, this work has reached the public in pieces, often as a part of pamphlets with limited circulation. This edition, which includes an introduction by Paul Kellogg that contextualizes the work and reintroduces Martov as an important thinker to a twenty-first century readership, makes Martov's work available in its complete form for the first time in a hundred years.